2021
DOI: 10.3390/molecules26082302
|View full text |Cite
|
Sign up to set email alerts
|

Lignin as a Partial Polyol Replacement in Polyurethane Flexible Foam

Abstract: This study was focused on evaluating the suitability of a wide range of lignins, a natural polymer isolated from different plant sources and chemical extractions, in replacing 20 wt.% of petroleum-based polyol in the formulation of PU flexible foams. The main goal was to investigate the effect of unmodified lignin incorporation on the foam’s structural, mechanical, and thermal properties. The hydroxyl contents of the commercial lignins were measured using phosphorus nuclear magnetic resonance (31P NMR) spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…A previous study demonstrated that the lignin macromolecules comprised higher content of hydroxyl groups than the polyether-based polyols. 31 Hence, lignin may react with more diisocyanate to form more urethane linkages, increasing the density of PU foams. The density of Lignin-1 and -2-based PU foams indicated that the Kraft lignin recovered at pH = 7 was more suitable than the Kraft lignin recovered at pH = 12 to produce the lower-density PU foams.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study demonstrated that the lignin macromolecules comprised higher content of hydroxyl groups than the polyether-based polyols. 31 Hence, lignin may react with more diisocyanate to form more urethane linkages, increasing the density of PU foams. The density of Lignin-1 and -2-based PU foams indicated that the Kraft lignin recovered at pH = 7 was more suitable than the Kraft lignin recovered at pH = 12 to produce the lower-density PU foams.…”
Section: Resultsmentioning
confidence: 99%
“…Such a difference between the lignin-based PU foams and control PU foams in the ultimate elongation was statistically significant ( P < 0.05), and it might be related to the rigid aromatic rings in the lignin macromolecules. 31 Moreover, the ultimate elongation of lignin-based PU foams was observed to rely on the lignin categories, indicating that the flexibility and elasticity of lignin-based PU foams were indirectly affected by the lignin recovery processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEM was used to evaluate the morphology and microstructure of the surface and cross-section of PU-NL foam and PU-NL/EEP wound dressing ( Figure 3 ). This characteristic is important as the mechanical performance of the foam is highly influenced by the average cell size and the thickness of cell walls [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…A range below 100 nm is evident for lignin as nanoparticles. Generally, lignin-based polyurethane foams produce smaller cell sizes and thicker cell walls than the pure PU, which might be due to the nucleating agent role of NL, explaining the higher density values and mechanical properties [ 48 ].…”
Section: Resultsmentioning
confidence: 99%